RMAC study: A randomized study for evaluation of metronomic adjuvant chemotherapy in recurrent head and neck cancers post salvage surgical resection in those who are ineligible for re-irradiation. (May 2022) - Patil, Vijay; Noronha, Vanita; Joshi, Amit; Menon, Nandini; Mathrudev, Vijayalakshmi; Bhattacharjee, Atanu; Chandrasekharan, Arun; Vallathol, Dilip; Dsouza, Hollis; Srinivas, Sujay; Mandal, Tanmay; Chaturvedi, Pankaj; et al.
Highlights: The first randomised study on adjuvant metronomic therapy in recurrent head and neck cancer who have undergone salvage resection and are ineligible for re-radiation. Disease-free interval is more in patients on the observation arm than on metronomic adjuvant chemotherapy. Overall survival is better in patients on the observation arm than on metronomic adjuvant chemotherapy. Abstract: Background: Adjuvant re-chemoradiation after salvage surgery improves disease-free survival in recurrent head and neck cancer. However, most patients are ineligible for re-irradiation and are kept on observation. We investigated the efficacy of metronomic adjuvant chemotherapy (MAC) in this group of patients compared to observation. Methods: This was a randomized integrated phase II/III clinical trial. Adults with recurrent head and neck cancer, who had undergone salvage surgery, but were ineligible for adjuvant re-irradiation were randomized in a 1:1 ratio to either MAC arm or observation. MAC consisted of weekly oral methotrexate (at a dose of 15 mg per square meter of body surface area) and celecoxib (at a dose of 200 mg orally twice daily) for 6 months. The primary endpoint of phase 2 was disease-free survival (DFS) while that of phase 3 was overall survival (OS). For phase 2, to detect an improvement in the hazard ratio (HR) 0.67 with MAC, with a type 1 error of 10% (1-sided), type 2 error of 30%, 105 patients were required. While for phase 3, with a target HR of 0.77, with a type 1 error of 5%, type 2 error of 20%, 318 patients were required. Here we report the results of phase 2 part of the study. Results: At a median follow up of 30.2 months (95% confidence interval (CI), 25.3 to 35.1) the 1 year and 2-year DFS were 57.4% (95% CI, 42.8–69.5) and 37.6% (95% CI, 24.1–51) in MAC arm whereas the corresponding numbers were 62.3% (95% CI, 47.8 to 73.8) and 54.2%(95% CI, 39.8 to 66.5) in observation arm, respectively (hazard ratio for progression, 1.45; 95% CI, 0.87 to 2.47; P = 0.15). In the MAC arm, the 1 and 2 year OS was 78.7% (95% CI, 64.9 to 87.6) and 48% (95% CI, 34.1 to 62).The corresponding figures in the observation arm were 79.2% (95% CI, 65.7 to 87.9) and 65.5% (95% CI, 50.9 to 76.7) (hazard ratio for death, 1.7, 95% CI, 0.94 to 3.08; P = 0.08). Conclusion: The adjuvant 6-month metronomic schedule was ineffective in improving outcomes in recurrent head and neck cancers post salvage surgery who are ineligible for re-radiation. Trial registration. Clinical trial registry of India (CTRI)- CTRI/2016/04/006872 [Registered on 26/4/2016]